Build A Strong Brand Image in Waste Management Social Enterprises - Dhita, Tiara Alunan; Rudito, Bambang (Journal of Business and Management, 2021)
Social enterprises of waste management have been growing rapidly overtime. During the pandemic, this sector has become one of the resilient businesses where enterprises should be able to attract attention and become on top of mind with a good perception for customers. Moreover, there is currently no single company that has a strong waste management brand image. This study aims to identify the factors to build brand image, identify most significant factors which affect the improvement of brand image, and provide recommendations on how companies should build strong brand image. The data collection was carried out using a quantitative approach and purposive sampling technique with a total of 101 respondents. PLS-SEM is used to process data and analyze the relationship between variables. In addition, a qualitative approach through semi-structured interviews with 3 informants was conducted to validate data and develop recommendations. The results showed that aspects of brand behavior and attitudes and brand associations had a significant effect on the formation of the brand image of waste management social enterprises, while the other three aspects such as brand identity, brand personality, and brand competence and benefits did not show a significant effect. This study recommends waste management social enterprises can implement carrying out certain live acts, spreading positive state of mind, conducting social interaction, and holding collective acts to build brand image. Keywords: Waste Management Social Enterprises, Brand Image, Quantitative Approach, PLS-SEM,Qualitative Approach